Cometary Ionospheres: An Updated Tutorial - Beth,A; Galand,M; Simon,Wedlund C; Eriksson,A (University of Arizona Press, 2022)
This chapter aims at providing the tools and knowledge to understand and model the plasma environment surrounding comets in the innermost part near the nucleus. In particular, our goal is to give an updated post-Rosetta view of this ionised environment: what we knew, what we confirmed, what we overturned, and what we still do not understand.